Perivascular Lymphocyte Clusters Induced by Gastric Subserous Layer Vaccination Mediate Optimal Immunity against Helicobacter through Facilitating Immune Cell Infiltration and Local Antibody Response - Chupeng Hu; Wei Liu; Ningyin Xu; An Huang; Zhiqin Zeng; Shuanghui Luo; Zhenxing Zhang; Menghui Fan; Feng Ye; Tao Xi; Yingying Xing (Journal of Immunology Research)
Background. In situ vaccination-induced local inflammatory response resulted in the establishment of a pool of tissue-resident memory T (TRM) cells and new vessels after the resolution of inflammation. TRM cells have received increasing attention; however, the role of new vessels in protective response is still unknown. Materials and Methods. We performed the laparotomy to access the stomach and injected alum-based vaccine into the gastric subserous layer (GSL). At 28 days post vaccination, a parabiosis mouse model along with depletion of anti-CD90.2 antibody was employed to explore the function of perivascular lymphocyte clusters in recall responses. The composition of the gastric lymphocyte clusters was analyzed by immunofluorescence staining. Antibody responses were detected using ELISA. Gastric lymphocytes were analyzed using flow cytometry. Results. GSL vaccination induced the formation of new vessels in the inflamed region. These new vessels were different from native vessels in that they were generally accompanied by perivascular lymphocyte clusters that mainly consisted of CD90-expressing cells. Additionally, histological analysis revealed the presence of CD4+ and CD8+ T cells in the perivascular lymphocyte clusters. Administration of a dose of an anti-CD90.2 antibody to GSL-vaccinated mice resolved these clusters. The efficacy of protection was compared in the parabiosis mice. Upon challenge, the presence of perivascular lymphocyte clusters was responsible for the fast recall response, as depletion of these clusters by CD90.2 antibody administration resulted in decreased expressions of VCAM-1, Madcam-1, and TNF-α, as well as lower recruitment of proinflammatory immune cells, decreased antibody levels, and poor protection. Conclusions. Our research demonstrates that in situ vaccination-induced regional inflammatory response contributes to optimal recall response not only by establishing a CD4+ TRM pool but also by creating an “expressway,” i.e., perivascular lymphocyte cluster.